ABCD (Asset Based Communities Development): Legalitas dan Pengembangan Potensi Usaha Mikro, Kecil, dan Menengah (UMKM) Telor Asin Desa Pagelaran - Lisa Agustina (Pusat Riset dan Inovasi Nasional, 2024)
The basic idea of community service is based on the problematic situation faced by partners, namely regarding the management of the village's superior potential. Community service activities are carried out in the form of knowledge sharing with an andragogical approach. This research was conducted using the ABCD (Asset Based Communities Development) approach which is a model approach in community development. This development focuses on an inventory of assets in the community that are seen as supporting community empowerment activities. After conducting interviews with informants through purposive sampling techniques and in-depth observations by looking at the potential of Pagelaran village, it was found that potential problems with Micro, Small and Medium Enterprises (MSMEs) processing the largest salted eggs as a home industry that process the greatest potential of Pagelaran village, namely salted eggs which are still managed traditionally and do not have a valid business license. The solution offered based on these potential findings is to make business patents through legality and development of the potential of Salted Egg Micro, Small and Medium Enterprises (MSMEs) in Pagelaran Village.